Political and legal discourse on the concept of “religious extremism” (Journal of Philosophy Culture and Political Science, 2018)
In Kazakhstan, the problem of “religious extremism” and “terrorism” as a criminal act is not only cognitive signifi cance, they are now among the important practical problems of the state. Because this problem is directly related to national security. Kazakhstan, which establishes an open society, affect the main tendency that occur in the global arena. All the contradictions and the threat of world globalization affect our state. In connection with this problem now, “religious extremism” are devoted to ensuring the national security of the state and the defi nition of priorities and resources. Keywords: discourse, religion, religious extremism, ideology, confession, right, radicalism, political extremism, terrorism, organization, national security, extremism, ethnic extremism.